Pendampingan Standardisasi Produk Sebagai Alternatif Peningkatan Pemasaran Pada UMKM di Desa Ngargogondo, Borobudur - Andhatu Achsa; Dian Marlina Verawati; Ivo Novitaningtyas (Universitas Mathla'ul Anwar Banten, 2022)
PRODUCT STANDARDIZATION AS AN ALTERNATIVE TO INCREASING MARKETING FOR MSMES IN NGARGOGONDO VILLAGE, BOROBUDUR. This program is motivated by the needs of partners for product marketing development. The purpose of this program is to increase partners' understanding and ability to standardize products, partners' understanding of the importance of PIRT and halal certification, and increase partners' understanding of PIRT licensing and halal certification for products. The program was implemented using the method of socialization, lectures, and tutorials for 20 MSME actors in Ngargogondo Village as program targets. The results of the program implementation show that there is an increase in partners' understanding of the importance of PIRT licensing and halal certification for products. Through the implementation of this program, it is hoped that consumer buying interest in MSME products in Ngargogondo Village will increase so that it has an impact on increasing sales volume and being a solution to partner problems.